'Mito-Bomb': a novel mitochondria-targeting nanosystem for ferroptosis-boosted sonodynamic antitumor therapy. (31st December 2022) - Wang, Jianxin; Zhao, Zhiyu; Liu, Yan; Cao, Xinyu; Li, Fuxin; Ran, Haitao; Cao, Yang; Wu, Changjun
Abstract: Mitochondria play an important role in regulating tumor cell death and metabolism so that they can be potential therapeutic targets. Sonodynamic therapy (SDT) represents an attractive antitumor method that induces apoptosis by producing highly toxic reactive oxygen species (ROS). Mitochondria-targeting SDT can cause oxidative damage and improve the efficiency of tumor therapy. However, due to the nonselective distribution of nanosystems and the anti-apoptotic mechanism of cancer cells, the therapeutic effect of SDT is not ideal. Therefore, we proposed a novel mitochondria-targeting nanosystem ('Mito-Bomb') for ferroptosis-boosted SDT. Sonosensitizer IR780 and ferroptosis activator RSL-3 were both encapsulated in biocompatible poly(lactic‐ co ‐glycolic acid) (PLGA) nanoparticles to form 'Mito-Bomb' (named IRP NPs). IR780 in this nanosystem was used to mediate mitochondria-targeting SDT. RSL-3 inhibited the activity of GPX4 in the antioxidant system to induce ferroptosis of tumor cells, which could rewire tumor metabolism and make tumor cells extremely sensitive to SDT-induced apoptosis. Notably, we also found that RSL-3 can inhibit hypoxia inducible factor-1α (HIF-1α) and induce ROS production to improve the efficacy of SDT to synergistically antitumor. RSL-3 was applied as a 'One-Stone-Three-Birds' agent for cooperatively enhanced SDT against triple-negative breast cancer. This study presented the first example of RSL-3 boosting mitochondria-targeting SDT as a ferroptosis activator. The 'Mito-Bomb' biocompatible nanosystem was expected to become an innovative tumor treatment method and clinical transformation.